Plasmodium vivax Malaria Viewed through the Lens of an Eradicated European Strain. (7th November 2019) - van Dorp, Lucy; Gelabert, Pere; Rieux, Adrien; de Manuel, Marc; de-Dios, Toni; Gopalakrishnan, Shyam; Carøe, Christian; Sandoval-Velasco, Marcela; Fregel, Rosa; Olalde, Iñigo; Escosa, Raül; Aranda, Carles; et al.
Abstract: The protozoan Plasmodium vivax is responsible for 42% of all cases of malaria outside Africa. The parasite is currently largely restricted to tropical and subtropical latitudes in Asia, Oceania, and the Americas. Though, it was historically present in most of Europe before being finally eradicated during the second half of the 20th century. The lack of genomic information on the extinct European lineage has prevented a clear understanding of historical population structuring and past migrations of P. vivax . We used medical microscope slides prepared in 1944 from malaria-affected patients from the Ebro Delta in Spain, one of the last footholds of malaria in Europe, to generate a genome of a European P. vivax strain. Population genetics and phylogenetic analyses placed this strain basal to a cluster including samples from the Americas. This genome allowed us to calibrate a genomic mutation rate for P. vivax, and to estimate the mean age of the last common ancestor between European and American strains to the 15th century. This date points to an introduction of the parasite during the European colonization of the Americas. In addition, we found that some known variants for resistance to antimalarial drugs, including Chloroquine and Sulfadoxine, were already present in this European strain, predating their use. Our results shed light on the evolution of an important human pathogen and illustrate the value of antique medical collections as a resource for retrieving genomic information on pathogens from the past.